2015
DOI: 10.1038/onc.2015.326
|View full text |Cite
|
Sign up to set email alerts
|

Targeting colorectal cancer via its microenvironment by inhibiting IGF-1 receptor-insulin receptor substrate and STAT3 signaling

Abstract: The tumor microenvironment (TME) exerts critical pro-tumorigenic effects through cytokines and growth factors that support cancer cell proliferation, survival, motility and invasion. Insulin-like growth factor-1 (IGF-1) and Signal transducer and activator of transcription 3 (STAT3) stimulate colorectal cancer (CRC) development and progression via cell autonomous and microenvironmental effects. Using a unique inhibitor, NT157, which targets both IGF-1 receptor (IGF-1R) and STAT3, we show that these pathways reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
123
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 49 publications
4
123
1
6
Order By: Relevance
“…For this reason, we examined the expression of several chemokines in CRC and preliminarily verified the upregulation of CXCL5 in CRC. Previous studies have reported that CXCL5 produced by fibroblasts plays a prominent role in the progression, growth and spread of various types of cancer [15, 21]. However, in our study, we revealed that CRC cells, rather than fibroblasts, are able to secrete CXCL5.…”
Section: Discussioncontrasting
confidence: 75%
“…For this reason, we examined the expression of several chemokines in CRC and preliminarily verified the upregulation of CXCL5 in CRC. Previous studies have reported that CXCL5 produced by fibroblasts plays a prominent role in the progression, growth and spread of various types of cancer [15, 21]. However, in our study, we revealed that CRC cells, rather than fibroblasts, are able to secrete CXCL5.…”
Section: Discussioncontrasting
confidence: 75%
“…In various studies, overactivated IGF‐1R is identified in the progression, development, and targeted agent resistance of various human cancers including CRC (Afshar et al, ; Denduluri et al, ; Moreno‐Acosta et al, ; Simpson, Petnga, Macaulay, Weyer‐Czernilofsky, & Bogenrieder, ). For instance, study by Sanchez‐Lopez () have demonstrated that IGF‐1R plays key roles in different mechanisms including cellular growth, proliferation, angiogenesis, and metastasis in CRC, and thus could be a valid candidate for the therapy of human CRC. Furthermore, in another study, it has been suggested that IGF‐1R significantly associated with poor overall survival and then resistance to chemotherapy in metastatic tumors compared to primary ones (Codony‐Servat et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among NT compounds, NT157 showed to prevent colorectal tumor development and caused durable regression of established tumors and attenuated metastatic growth in murine models and in human CRC cells. 28 .…”
Section: Discussionmentioning
confidence: 99%